Dental resin-reinforced glass ionomer cement composition

By adding organic and inorganic composite fillers or pore organic fillers to dental resin-reinforced glass ionic cement adhesive, the problem of thread head phenomenon after extrusion is solved, the operation fluency and safety is improved, the treatment time is shortened and the infection risk is reduced.

JP2025058784APending Publication Date: 2025-04-09SHOFU INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023168928
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Dental resin-reinforced glass ionic cement adhesives are prone to thread heads after initial extrusion, which affects the smoothness and safety of operation, and extends the treatment time and increases the risk of infection.

Method used

Add appropriate amounts of organic and inorganic composite fillers or pore organic fillers to dental resin-reinforced glass ionic cement adhesive, and adjust their composition ratio to reduce the occurrence of thread head phenomena after extrusion.

Benefits of technology

It effectively reduces the occurrence of thread head after extrusion, improves the fluency and safety of filling and application on dental denture equipment, shortens treatment time, and reduces the risk of infection, while maintaining good extrusion and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058784000001
    Figure 2025058784000001
  • Figure 2025058784000002
    Figure 2025058784000002
  • Figure 2025058784000003
    Figure 2025058784000003
Patent Text Reader

Abstract

To provide a dental resin-reinforced glass ionomer cement composition that has little stringiness of a mixed product, can be shaped quickly after mixing, has excellent cavity filling properties and application properties to dental prosthetic devices, and has good mixability and mechanical properties.SOLUTION: A dental resin-reinforced glass ionomer cement composition comprises (a) an acid-reactive glass powder, (b) a polyalkenoic acid, (c) water, (d) a polymerizable monomer, (e1) an organic-inorganic composite filler, and / or (e2) a porous organic filler in an amount of 1 mass% or more and 30 mass% or less, and (f) a polymerization initiator.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dental resin-reinforced glass ionomer cement composition for repairing teeth whose shape has been partially damaged mainly due to caries, fractures, etc., or for bonding or adhering a dental prosthetic device to a tooth whose shape has been damaged. [Background technology]

[0002] In clinical dentistry, direct restoration is performed by filling the tooth with a filling material, and indirect restoration is performed by bonding and / or adhering a dental prosthesis to the tooth using a bonding material in order to restore the aesthetics and function of teeth that have been partially damaged by caries, fractures, etc. Dental resin-reinforced glass ionomer cement is one of the representative filling and bonding materials.

[0003] Dental resin-reinforced glass ionomer cements generally consist of polyalkenoic acid, water, acid-reactive glass powder such as fluoroaluminosilicate glass, polymerizable monomer, and polymerization initiator as main components, and are in the form of powder-liquid or two-paste type. In addition, these types of dental resin-reinforced glass ionomer cements are mixed by hand or machine in the powder-liquid type, and mixed by hand or automatically using a mixing tip in the two-paste type, so that the acid-base reaction between the polyalkenoic acid and the acid-reactive glass powder as well as the chemical polymerization reaction of the polymerizable monomer are initiated, and hardening proceeds. In addition, some types can be hardened by photopolymerization by further adding a photopolymerization initiator.

[0004] Dental resin-reinforced glass ionomer cement has features such as sustained release of fluoride ions over a long period of time, high transparency, mechanical properties, etc. In addition, when photocuring properties are imparted, the composition can be cured by irradiating light at the time the surgeon intends, which has the advantage that there is no need to wait for curing.

[0005] Patent Document 1 discloses a technology in which a tri- or higher functional (meth)acrylamide-based polymerizable monomer is added to the general main component of the above-mentioned dental resin-reinforced glass ionomer cement, thereby achieving high surface hardening properties even when moistened, excellent color resistance, and small expansion due to water absorption. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2021-031409 Summary of the Invention [Problem to be solved by the invention]

[0007] Since dental resin-reinforced glass ionomer cement contains a highly viscous polyalkenoic acid aqueous solution in its composition, the kneaded material immediately after kneading tends to be stringy. This stringiness may have a negative effect on the operability during filling and bonding, and is particularly susceptible to the influence during filling operations. For example, after the kneaded material immediately after kneading is filled into a cavity using a dental instrument such as an instrument or a dental syringe, if the kneaded material becomes stringy when the dental instrument is removed from the kneaded material, the kneaded material may adhere to the surrounding tooth structure and oral mucosa. In such cases, it is necessary to carefully remove the attached material, making the operation complicated.

[0008] In addition, since the dental resin-reinforced glass ionomer cement hardens due to the acid-base reaction and chemical polymerization immediately after mixing, the stringiness of the mixed material decreases after a certain period of time regardless of the nature of the mixed material, making it easier to perform the shaping operation. Therefore, when shaping the mixed material filled in the cavity, the shaping operation is performed after waiting until the stringiness of the mixed material decreases. On the other hand, if the mixed material is significantly stringy and it takes time to reduce the stringiness, the treatment time will be longer and the risk of the treatment site being contaminated by saliva will increase.

[0009] On the other hand, as a method for reducing the stringiness of the kneaded material immediately after kneading, a method for increasing the proportion of acid-reactive glass powder contained in the dental resin-reinforced glass ionomer cement or a method for increasing the particle size can be mentioned. However, when the proportion of acid-reactive glass powder is increased, the viscosity of the kneaded material increases, and therefore kneadability may decrease. In addition, when the particle size of the acid-reactive glass powder is increased, the acid-base reactivity of the acid-reactive glass powder and the polyalkenoic acid decreases, and therefore, the mechanical properties of the hardened material may decrease.

[0010] Therefore, an object of the present invention is to provide a dental resin-reinforced glass ionomer cement composition which causes less stringiness of the mixed product than conventional techniques, allows shaping operations to be carried out soon after mixing, has excellent cavity filling properties and application properties to dental prosthetic devices, and also has good kneading properties and mechanical properties. [Means for solving the problem]

[0011] As a result of intensive research conducted by the inventors in response to these problems, they discovered that by incorporating an organic-inorganic composite filler and / or a porous organic filler in a specific range into a dental resin-reinforced glass ionomer cement composition, the mixed product has less stringiness, excellent cavity filling properties and excellent applyability to dental prosthetic devices, and furthermore, the mixed product becomes in a state where shaping operations can be performed quickly after completion of mixing, and the mixed product exhibits good mixing properties and excellent mechanical properties, thereby completing the present invention.

[0012] That is, the above problems can be solved by using the following component configuration. (a) acid-reactive glass powder; (b) polyalkenoic acid, (c) water; (d) a polymerizable monomer; (e1) an organic-inorganic composite filler, and / or (e2) a porous organic filler, 1% by mass or more and 30% by mass or less, and (f) a polymerization initiator, A dental resin-reinforced glass ionomer cement composition comprising: Effect of the Invention

[0013] According to the present invention, it is possible to provide a dental resin-reinforced glass ionomer cement composition which exhibits little stringiness immediately after mixing, which allows for excellent cavity filling properties and excellent application properties to dental prosthetic devices, and which is ready for shaping operations soon after mixing, thereby shortening treatment time, while also exhibiting excellent mixability and mechanical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. As used herein, the term "dental resin-reinforced glass ionomer cement composition" refers to a dental hardenable composition that hardens through a polymerization reaction of a compound having a polymerizable group, such as a polymerizable monomer, an oligomer having a polymerizable group, and / or a polymer having a polymerizable group, and through an acid-base reaction that occurs between an acid-reactive glass powder and a polyalkenoic acid in the presence of water.

[0015] In this specification, the degree of stringiness of the kneaded material was evaluated by the following method. That is, a kneaded material of a dental resin-reinforced glass ionomer cement composition (specified as a total amount of 360 mg) was filled into a simulated cavity of a certain size, the excess was scraped off to make the surface flat, and then 10 seconds after the end of kneading, the cylindrical tip of a metal instrument (diameter: φ1.5 mm) was vertically immersed 0.5 mm into the kneaded material, and the degree of stringiness was confirmed when the instrument was immediately gently pulled up. This test was performed in an environment with a temperature of 23 ± 1 ° C and a humidity of 50 ± 10%. If the kneaded material did not string or had only a slight stringiness, it was judged to have "good kneaded material properties with little stringiness".

[0016] In addition, the degree of stringiness of the kneaded product was evaluated using the same method, and the time when the kneaded product had "good properties with little stringiness" was taken as the "time when shaping could begin."

[0017] In this specification, the term "polyalkenoic acid" refers to a polymer containing an ethylenically unsaturated monomer unit having an acidic group. In addition, in this specification, (meth)acrylate refers to both acrylate and methacrylate, (meth)acryloyl refers to both acryloyl and methacryloyl, and (meth)acrylamide refers to acrylamide and methacrylamide.

[0018] In addition, in this specification, the term "50% particle size (D50)" refers to the particle size at which the integrated value from the small particle size side becomes 50% in the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device.

[0019] In using the dental resin-reinforced glass ionomer cement composition of the present invention, for example, a kneading device for capsules for dental restorative materials and a capsule for mixing and dispensing dental materials can be used. Conventionally, in the dental field, capsules for dental cement have been widely used as containers for two-component mixed and kneaded dental cement. When using capsules for dental cement, the two components are mixed and kneaded using an automatic mixer such as a capsule mixer, and then a filling tool such as an applier is attached to the capsule to fill the dental cement inside the capsule into the application site such as a cavity.

[0020] In addition, in this specification, the term "average pore size" refers to the average size of pores present in each particle, calculated from the pore size distribution measured using a mercury intrusion porosimetry apparatus. Note that this average pore size is different from the aggregated pores formed by the aggregation of particles.

[0021] In this specification, the "specific surface area" is a value determined by measuring the amount of nitrogen adsorbed on the particle surface by the BET method.

[0022] The dental resin-reinforced glass ionomer cement composition of the present invention contains (a) acid-reactive glass powder, (b) polyalkenoic acid, (c) water, (d) polymerizable monomer, specific amount of (e1) organic-inorganic composite filler, and / or (e2) porous organic filler, and (f) polymerization initiator as essential components, and by using this component composition, the kneaded product has less stringiness, excellent cavity filling properties and excellent application properties to dental prosthetic devices, and can be shaped quickly after kneading, while also exhibiting good kneadability and excellent mechanical properties. The above components of the present invention will be described in detail below.

[0023] <(a) Acid-reactive glass powder> The (a) acid-reactive glass powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention must contain an acid-reactive element such as a metal element, and a fluorine element. The (a) acid-reactive glass powder contains an acid-reactive element, and in the presence of (c) water, an acid-base reaction with the acidic group of the (b) polyalkenoic acid proceeds. Specific examples of the acid-reactive element include, but are not limited to, sodium, potassium, calcium, strontium, barium, lanthanum, aluminum, zinc, etc. These acid-reactive elements may be contained in one type or in two or more types, and the content of these elements is not particularly limited.

[0024] Furthermore, in order to impart X-ray contrast to the dental resin-reinforced glass ionomer cement composition of the present invention, it is preferable that the acid-reactive glass powder (a) contains a radiopaque element. Specific examples of radiopaque elements include, but are not limited to, strontium, lanthanum, zirconium, titanium, yttrium, ytterbium, tantalum, tin, tellurium, tungsten, and bismuth. In addition, there is no particular restriction on other elements contained in the acid-reactive glass powder (a), and the acid-reactive glass powder (a) of the present invention can contain various elements.

[0025] (a) Examples of acid-reactive glass powders include aluminosilicate glass, borosilicate glass, aluminoborate glass, boroaluminosilicate glass, phosphate glass, borate glass, and silicate glass, each of which contains the above-mentioned acid-reactive elements, fluorine, and an X-ray opaque element, but are not limited to these.

[0026] Furthermore, the particle shape of the (a) acid-reactive glass powder is not particularly limited, and any particle shape such as spherical, needle-like, plate-like, crushed, scale-like, etc. can be used without any restriction. These (a) acid-reactive glass powders can be used alone or in combination of several kinds.

[0027] The method for producing these (a) acid-reactive glass powders is not particularly limited, and any method such as a melting method, a gas phase method, a sol-gel method, etc. can be used without any problem. Among these, it is preferable to use the (a) acid-reactive glass powder produced by the melting method or the sol-gel method, which are easy to control the type and content of elements.

[0028] (a) The acid-reactive glass powder can be used after being pulverized to a desired particle size. The pulverization method is not particularly limited, and either wet or dry pulverization can be used. Specifically, the raw glass can be pulverized using a high-speed rotary mill such as a hammer mill or turbo mill, a container-driven mill such as a ball mill, planetary mill or vibration mill, a media-agitating mill such as an attritor or bead mill, or a jet mill, and the particle size can be appropriately adjusted according to the desired properties to be imparted to the dental resin-reinforced glass ionomer cement composition of the present invention.

[0029] The 50% particle size (D50) of the (a) acid-reactive glass powder used in the dental resin-reinforced glass ionomer cement composition of the present invention is preferably 0.5 μm or more and 20 μm or less. The dental resin-reinforced glass ionomer cement composition of the present invention can contain only acid-reactive glass powder having a 50% particle size (D50) of 0.5 μm or more and 20 μm or less as the (a) acid-reactive glass powder.

[0030] In addition, when the dental resin-reinforced glass ionomer cement composition of the present invention is used as a filling material, the 50% particle size (D50) of the (a) acid-reactive glass powder is preferably 2 μm or more and 20 μm or less in order to achieve a high elastic modulus. When the dental resin-reinforced glass ionomer cement composition of the present invention is used as a filling material, the (a) acid-reactive glass powder may contain only an acid-reactive glass powder having a 50% particle size (D50) of 2 μm or more and 20 μm or less. On the other hand, when the dental resin-reinforced glass ionomer cement composition of the present invention is used as a material for luting, the 50% particle size (D50) of the (a) acid-reactive glass powder is preferably 0.5 μm or more and 10 μm or less in order to achieve a thin coating thickness, and more preferably 0.5 μm or more and 5 μm or less. When the dental resin-reinforced glass ionomer cement composition of the present invention is used as a material for bonding, (a) the acid-reactive glass powder may contain only acid-reactive glass powder having a 50% particle size (D50) of 0.5 μm or more and 10 μm or less.

[0031] (a) When the 50% particle size (D50) of the acid-reactive glass powder is less than 0.5 μm, its surface area increases and it becomes impossible to include a large amount of the powder in the composition, which may result in a decrease in mechanical properties and a shortened operating time.

[0032] (a) If the 50% particle size (D50) of the acid-reactive glass powder exceeds 20 μm, the mechanical properties may deteriorate.

[0033] In order to adjust the operability, hardening properties, mechanical properties, etc. of the dental resin-reinforced glass ionomer cement composition of the present invention, the (a) acid-reactive glass powder can be subjected to various surface treatments, heat treatments, or aggregation treatments in the liquid phase or gas phase, etc., within the scope of not adversely affecting the acid-base reaction with the (b) polyalkenoic acid. Moreover, these treatments can be performed alone or in combination of several types, and the order of each treatment is not particularly limited. Among these, surface treatments and heat treatments are preferred because they are easy to control various properties and have excellent productivity.

[0034] Specific examples of the surface treatment of the (a) acid-reactive glass powder include washing with an acid such as phosphoric acid or acetic acid, surface treatment with an acidic compound such as tartaric acid or polycarboxylic acid, surface treatment with a fluoride such as aluminum fluoride, and surface treatment with a silane compound such as (meth)acryloyloxymethyltrimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, partially hydrolyzed oligomer of tetramethoxysilane, and partially hydrolyzed oligomer of tetraethoxysilane. The surface treatments that can be used in the present invention are not limited to those described above, and these surface treatments can be used alone or in combination. Furthermore, there is no particular restriction on the amount of the surface treatment agent relative to the (a) acid-reactive glass powder when performing the surface treatment, and it may be appropriately adjusted according to the particle size of the (a) acid-reactive glass powder and the desired properties.

[0035] A specific example of the heat treatment of (a) the acid-reactive glass powder is a treatment method in which the powder is heated at 200° C. or more and 800° C. or less for 1 hour or more and 72 hours or less using an electric furnace, etc. The heat treatments that can be used in the present invention are not limited to those described above, and the treatment process can also be a treatment at a single temperature or a multi-stage treatment at multiple temperatures.

[0036] The content of the (a) acid-reactive glass powder is preferably 30% by mass or more and 80% by mass or less, more preferably 45% by mass or more and 80% by mass or less, based on the total amount of the dental resin-reinforced glass ionomer cement composition of the present invention. If the content of the (a) acid-reactive glass powder is less than 30% by mass, the mechanical properties may be deteriorated. If the content of the (a) acid-reactive glass powder is more than 80% by mass, the operation time may be shortened, or the viscosity of the kneaded product may increase, resulting in poor kneadability.

[0037] <(b) Polyalkenoic acid> The (b) polyalkenoic acid that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be any homopolymer or copolymer of an ethylenically unsaturated monomer having at least one carboxy group in the molecule, such as an ethylenically unsaturated monocarboxylic acid, an ethylenically unsaturated dicarboxylic acid, an ethylenically unsaturated tricarboxylic acid, etc. Furthermore, there is no problem even if the (b) polyalkenoic acid is a copolymer of an ethylenically unsaturated monomer that does not have a carboxy group in the molecule and an ethylenically unsaturated monomer that has a carboxy group.

[0038] Specific examples of ethylenically unsaturated monomers having a carboxy group that can be used to obtain (b) polyalkenoic acid include, but are not limited to, ethylenically unsaturated monocarboxylic acids such as (meth)acrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, and 2-cyanoacrylic acid, ethylenically unsaturated dicarboxylic acids such as mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, and citraconic acid, and ethylenically unsaturated tricarboxylic acids such as aconitic acid, 1-butene-1,2,4-tricarboxylic acid, and 3-butene-1,2,3-tricarboxylic acid. Among these, it is preferable to use (b) polyalkenoic acid synthesized using only acrylic acid as a starting material, or (b) polyalkenoic acid synthesized using two or more starting materials such as acrylic acid and maleic acid, acrylic acid and maleic anhydride, acrylic acid and itaconic acid, and acrylic acid and 3-butene-1,2,3-tricarboxylic acid.

[0039] The polymerization method used to obtain various (b) polyalkenoic acids is not particularly limited, and any method such as solution polymerization, suspension polymerization, emulsion polymerization, etc. can be used without any restrictions. In addition, the polymerization initiator and chain transfer agent used during polymerization can be known, and the amount of each of them added can be appropriately adjusted according to the desired properties. The (b) polyalkenoic acids thus obtained can be used alone or in combination.

[0040] The weight average molecular weight of the (b) polyalkenoic acid is preferably 30,000 or more and 300,000 or less. Here, the weight average molecular weight is the average molecular weight calculated based on the molecular weight distribution measured by gel permeation chromatography. If the weight average molecular weight of the (b) polyalkenoic acid is less than 30,000, the mechanical properties may be reduced. If the weight average molecular weight of the (b) polyalkenoic acid is more than 300,000, the operation time may be shortened, or the viscosity of the kneaded product may increase, resulting in poor kneading properties. The dental resin-reinforced glass ionomer cement composition of the present invention can contain only polyalkenoic acid having a weight average molecular weight of 30,000 or more and 300,000 or less as the (b) polyalkenoic acid.

[0041] In addition, (b) polyalkenoic acid can be used after neutralizing a part of its carboxyl groups with a basic compound in order to adjust the acid-base reactivity with (a) acid-reactive glass powder, so long as it does not adversely affect various properties. Examples of basic compounds used for neutralization include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, and lithium carbonate, and alkali metal bicarbonates such as sodium bicarbonate, potassium bicarbonate, and lithium bicarbonate. In addition, various amine compounds such as primary amines, secondary amines, and tertiary amines can be used without any problem, so long as they can maintain solubility in water after neutralization. As the amine compound, triethanolamine, diethanolamine, N-methyldiethanolamine, 2-dimethylaminoethyl (meth)acrylate, and the like can be suitably used.

[0042] The content of (b) polyalkenoic acid is preferably 0.5% by mass or more and 17% by mass or less, more preferably 3% by mass or more and 11% by mass or less, based on the total content of the dental resin-reinforced glass ionomer cement composition of the present invention. If the content of (b) polyalkenoic acid is less than 0.5% by mass, the mechanical properties may be deteriorated. If the content of (b) polyalkenoic acid is more than 17% by mass, the operation time may be shortened, or the viscosity of the kneaded product may increase, resulting in poor kneadability.

[0043] <(c)Water> (c) Water that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention functions as a solvent for dissolving (b) polyalkenoic acid, and is also a component for diffusing metal ions eluted from (a) the acid-reactive glass powder and inducing a crosslinking reaction with (b) polyalkenoic acid.

[0044] (c) Water may be used without any restrictions so long as it does not contain impurities that inhibit the acid-base reaction in the dental resin-reinforced glass ionomer cement composition of the present invention or that adversely affect the hardening properties or mechanical properties. However, it is preferable to use distilled water or ion-exchanged water.

[0045] The content of (c) water is preferably 0.5% by mass or more and 27% by mass or less, more preferably 2% by mass or more and 14% by mass or less, based on the total content of the dental resin-reinforced glass ionomer cement composition of the present invention. If the content of (c) water is less than 0.5% by mass, the working time may be shortened, or the viscosity of the kneaded product may increase, resulting in poor kneading properties. If the content of (c) water is more than 27% by mass, the mechanical properties may be reduced.

[0046] <(d) Polymerizable monomer> The polymerizable monomer (d) that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention is not particularly limited in its molecular structure, and any known polymerizable monomer can be used. That is, examples of the polymerizable unsaturated group that the polymerizable monomer has include, but are not limited to, a (meth)acryloyloxy group, a (meth)acrylamide group, a styryl group, a vinyl group, an allyl group, and the like. Among these polymerizable unsaturated groups, a (meth)acryloyloxy group or a (meth)acrylamide group is preferable because of its excellent polymerization rate. In addition, the number of polymerizable unsaturated groups that the polymerizable monomer has is also not particularly limited. The hydrocarbon group bonded to the polymerizable unsaturated group may be any of an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a combination thereof, and the hydrocarbon group may have any substituent such as an acidic group, a hydroxyl group, a halogen atom, an alkoxy group, an amino group, or a glycidyl group. Specific examples of the polymerizable monomer are shown below.

[0047] Examples of the monofunctional polymerizable monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate. Acrylate, stearyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, adamantyl (meth)acrylate, phenyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, isobornyl (meth)acrylate ) acrylate, allyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, (meth)acryloyloxyethyl methyl succinate, 2-(meth)acryloyloxyethyl (Meth)acrylic acid esters such as propionate, acetoacetoxyethyl (meth)acrylate, acetoacetoxypropyl (meth)acrylate, and acetoacetoxybutyl (meth)acrylate; silane compounds such as γ-(meth)acryloyloxypropyltrimethoxysilane and γ-(meth)acryloyloxypropyltriethoxysilane; amines such as 2-(N,N-dimethylamino)ethyl (meth)acrylate and 2-(N,N-diethylamino)ethyl (meth)acrylate; 2,2,Examples of the fluorine-containing (meth)acrylates include 2-trifluoroethyl (meth)acrylate, perfluorohexylethyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, and their (meth)acrylamides, as well as N-methylol (meth)acrylamide.

[0048] Examples of aromatic bifunctional polymerizable monomers include 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxyethoxyphenyl)- ... 2-(4-(meth)acryloyloxydiethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, and (meth)acrylamides thereof.

[0049] Examples of the aliphatic bifunctional polymerizable monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9- Examples of such acrylates include nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, glycerol-1,3-dimethacrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)ethane, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, 2-hydroxy-1,3-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, and (meth)acrylamides thereof.

[0050] Examples of the trifunctional or higher polymerizable monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and (meth)acrylamides thereof.

[0051] Examples of the urethane-based polymerizable monomer include (meth)acrylate compounds having a urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, or 3-chloro-2-hydroxypropyl (meth)acrylate, with an isocyanate compound, such as methylcyclohexane diisocyanate, methylene bis(4-cyclohexyl isocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methylmethylbenzene, or 4,4-diphenylmethane diisocyanate.

[0052] These polymerizable monomers have excellent compatibility with other hydrophilic components, so it is more preferable to use a hydroxyl group-containing polymerizable monomer having at least one hydroxyl group in the molecule and at least one (meth)acryloyloxy group or (meth)acrylamide group as a polymerizable unsaturated group. Specific examples of hydroxyl group-containing polymerizable monomers are shown below.

[0053] Examples of hydroxyl group-containing polymerizable monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, dipropylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2,3-dihydro Examples of the monomer units include monofunctional polymerizable monomers such as 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-naphthoxypropyl (meth)acrylate, and their (meth)acrylamides; and polyfunctional polymerizable monomers such as glycerol-1,3-dimethacrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, bisphenol A diglycidyl (meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, and their (meth)acrylamides. Further examples include polyfunctional polymerizable monomers in which two or more hydroxyl groups among hydroxyl groups of sugar alcohols (erythritol, arabinitol, xylitol, ribitol, iditol, galactitol, sorbitol, mannitol, etc.), monosaccharides (arabinose, xylose, mannose, galactose, fructose, etc.), disaccharides (sucrose, maltose, lactose, trehalose, etc.), and trisaccharides (maltotriose, raffinose, etc.) are substituted with (meth)acryloyloxy groups or (meth)acrylamide groups.

[0054] In addition to the above polymerizable monomers, an acidic group-containing polymerizable monomer containing at least one acidic group in the molecule can be included as desired in order to improve adhesion to teeth, base metals, alumina, zirconia, etc. Examples of the acidic group contained in the acidic group-containing polymerizable monomer include a phosphate group, a pyrophosphate group, a phosphonic acid group, a carboxy group, a sulfonic acid group, and a thiophosphate group. Specific examples of the acidic group-containing polymerizable monomer are given below.

[0055] Examples of the phosphoric acid group-containing polymerizable monomer include (meth)acryloyloxymethyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, and the like. acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyeicosyl dihydrogen phosphate hydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, bis[3-(meth)acryloyloxypropyl]hydrogen phosphate, bis[4-(meth)acryloyloxybutyl]hydrogen phosphate, bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate, bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate, bis[9-(meth)acryloyloxynonyl]hydrogen phosphate, bis[10-(meth)acryloyloxyethyl]hydrogen phosphate, Examples of the hydrogen phosphate include 1,3-di(meth)acryloyloxypropyl-2-dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-2'-bromoethyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-(4-methoxyphenyl)hydrogen phosphate, and 2-(meth)acryloyloxypropyl-(4-methoxyphenyl)hydrogen phosphate.

[0056] Examples of the pyrophosphate group-containing polymerizable monomer include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[3-(meth)acryloyloxypropyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[5-(meth)acryloyloxypentyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[7-(meth)acryloyloxyheptyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, bis[9-(meth)acryloyloxynonyl] pyrophosphate, bis[10-(meth)acryloyloxydecyl] pyrophosphate, bis[12-(meth)acryloyloxydodecyl] pyrophosphate, tris[2-(meth)acryloyloxyethyl] pyrophosphate, and tetra[2-(meth)acryloyloxyethyl] pyrophosphate.

[0057] Examples of the phosphonic acid group-containing polymerizable monomer include 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and (meth)acryloyloxyethyl phenylphosphonate.

[0058] Examples of the carboxyl group-containing polymerizable monomer include (meth)acrylic acid, 2-chloroacrylic acid, 3-chloro(meth)acrylic acid, 2-cyanoacrylic acid, 1,4-di(meth)acryloyloxyethylpyromellitic acid, 6-(meth)acryloyloxynaphthalene-1,2,6-tricarboxylic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, 4-(meth)acryloyloxyethyltrimellitic acid and its anhydride, 4-(meth)acryloyloxybutyltrimellitic acid and its anhydride, 2-(meth)acryloyloxybenzoic acid, β-(meth)acryloyloxyethylhydrogensuccinate, β-(meth)acryloyloxyethylhydrogenmaleate, Examples of the acryloyloxy-1,1-undecanedicarboxylic acid include 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, p-vinylbenzoic acid, 4-(meth)acryloyloxyethoxycarbonylphthalic acid, 4-(meth)acryloyloxybutyloxycarbonylphthalic acid, 4-(meth)acryloyloxyhexyloxycarbonylphthalic acid, 4-(meth)acryloyloxyoctyloxycarbonylphthalic acid, 4-(meth)acryloyloxydecyloxycarbonylphthalic acid, and anhydrides thereof, 5-(meth)acryloylaminopentylcarboxylic acid, 6-(meth)acryloyloxy-1,1-hexanedicarboxylic acid, 8-(meth)acryloyloxy-1,1-octanedicarboxylic acid, 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid, and 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid.

[0059] Examples of the sulfonic acid group-containing polymerizable monomer include 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, 2-sulfoethyl (meth)acrylate, 4-(meth)acryloyloxybenzenesulfonic acid, and 3-(meth)acryloyloxypropanesulfonic acid.

[0060] Examples of the thiophosphate group-containing polymerizable monomer include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyethyl dihydrogen thiophosphate, 9-(meth)acryloyloxyethyl dihydrogen thiophosphate, 10-(meth)acryloyloxyethyl dihydrogen thiophosphate, 11-(meth)acryloyloxyethyl dihydrogen thiophosphate, 12-(meth)acryloyloxyethyl dihydrogen thiophosphate, 13-(meth)acryloyloxyethyl dihydrogen thiophosphate, 14-(meth)acryloyloxyethyl dihydrogen thiophosphate, 15-(meth)acryloyloxyethyl dihydrogen thiophosphate, 16-(meth)acryloyloxyethyl dihydrogen thiophosphate, 17-(meth)acryloyloxyethyl dihydrogen thiophosphate, 18-(meth)acryloyloxyethyl dihydrogen thiophosphate, 19-(meth)acryloyloxyethyl dihydrogen thiophosphate, 20-(meth)acryloyloxyethyl dihydrogen thiophosphate, 21-(meth)acryloyloxyethyl dihydrogen thiophosphate, 22-(meth)acryloyloxyethyl dihydrogen thiophosphate, 23-(meth)acryloyloxyethyl dihydrogen thiophosphate, 24-(meth)acryloyloxyethyl dihydrogen thiophosphate, 25-(meth)acryloyloxyethyl dihydrogen thiophosphate, 26-(meth)acryloyloxyethyl dihydrogen thiophosphate, 2 Examples of suitable acryloyloxyalkyl groups include 1-(meth)acryloyloxyalkyl groups, 2-(meth)acryloyloxyalkyl groups, and 3-(meth)acryloyloxyalkyl groups. Examples of suitable acryloyloxyalkyl groups include 1-(meth)acryloyloxyalkyl groups, 2-(meth)acryloyloxyalkyl groups, and 3-(meth)acryloyloxyalkyl groups. Examples of suitable acryloyloxyalkyl groups include 1-(meth)acryloyloxyalkyl groups, 2-(meth)acryloyloxyalkyl groups, and 3-(meth)acryloyloxyalkyl groups.

[0061] Among these acidic group-containing polymerizable monomers, it is preferable to use a carboxyl group-containing polymerizable monomer because of its excellent effect of improving adhesion, and it is more preferable to use a polymerizable monomer having two or more carboxyl groups. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain an acidic group-containing polymerizable monomer as the (d) polymerizable monomer.

[0062] In addition to the above polymerizable monomers, polymerizable monomers having a sulfur atom in the molecule, polymerizable monomers having a fluoro group, oligomers or polymers having at least one polymerizable group may be used. The above-mentioned polymerizable monomers are not limited to these, and may be used alone or in combination.

[0063] The content of the (d) polymerizable monomer is preferably 2% by mass or more and 48% by mass or less, more preferably 4% by mass or more and 36% by mass or less, based on the total dental resin-reinforced glass ionomer cement composition of the present invention. If the content of the (d) polymerizable monomer is less than 2% by mass, the chemical polymerization reaction and / or the photopolymerization reaction may not occur sufficiently, and the mechanical properties may be deteriorated. If the content of the (d) polymerizable monomer is more than 48% by mass, the compatibility of the (b) polyalkenoic acid, (c) water, and (d) polymerizable monomer may be deteriorated, and the cured product may become non-uniform, resulting in deterioration of the mechanical properties and transparency.

[0064] <(e1) Organic-inorganic composite filler> The (e1) organic-inorganic composite filler that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention is a composite particle consisting of an organic portion formed by hardening a polymerizable monomer and an inorganic portion contained in the form of an inorganic filler, and the inorganic filler is present in a state dispersed in the hardened polymerizable monomer. The (e1) organic-inorganic composite filler can be obtained by bringing a polymerizable monomer containing a polymerization initiator and an inorganic filler into a state as uniform as possible, hardening the polymerizable monomer, and pulverizing the hardened product as necessary.

[0065] The molecular structure of the polymerizable monomer that can be used to produce the (e1) organic-inorganic composite filler is not particularly limited, and the same polymerizable monomer as the above-mentioned (d) polymerizable monomer can be used.

[0066] The content of the polymerizable monomer contained in the raw material of (e1) organic-inorganic composite filler is preferably 15% by mass or more and 90% by mass or less, more preferably 15% by mass or more and 60% by mass or less. If the content of the polymerizable monomer in (e1) organic-inorganic composite filler is less than 15% by mass, the dispersion of the inorganic filler in (e1) organic-inorganic composite filler becomes insufficient, and the mechanical properties of the dental resin-reinforced glass ionomer cement composition of the present invention may be reduced. On the other hand, if the content of the polymerizable monomer exceeds 90% by mass, the wear resistance of the dental resin-reinforced glass ionomer cement composition of the present invention may be reduced.

[0067] Next, a polymerization initiator that can be used in the production of the organic-inorganic composite filler (e1) will be described. There is no particular restriction on the polymerization initiator, and known polymerization initiators such as photopolymerization initiators, chemical polymerization initiators, and thermal polymerization initiators can be used. Among them, it is preferable to use a thermal polymerization initiator because it has excellent production efficiency of the organic-inorganic composite filler. As the thermal polymerization initiator, organic peroxides such as benzoyl peroxide, azo compounds such as azobisisobutyronitrile, and the like can be suitably used. These polymerization initiators can be used alone or in combination regardless of the polymerization mode or polymerization method. There is no particular restriction on the amount of polymerization initiator added, but it is generally 0.1% by mass or more and 10% by mass or less with respect to 100% by mass of the total polymerizable monomers used in the production of the organic-inorganic composite filler (e1).

[0068] Next, the inorganic filler that can be used in the production of the (e1) organic-inorganic composite filler will be described. The inorganic filler is not particularly limited in its constituent elements, and known fillers can be used. Specific examples of the inorganic filler include inorganic oxides such as silica, alumina, titania, zirconia, strontium oxide, barium oxide, yttrium oxide, lanthanum oxide, and ytterbium oxide, inorganic composite oxides such as silica-zirconia, silica-titania, silica-titania-barium oxide, and silica-titania-zirconia, fused silica, quartz, aluminosilicate glass, fluoroaluminosilicate glass, borosilicate glass, aluminoborate glass, and boroaluminosilicate glass, and metal fluorides such as calcium fluoride, barium fluoride, strontium fluoride, yttrium fluoride, lanthanum fluoride, and ytterbium fluoride.

[0069] The shape of these inorganic fillers is not particularly limited, and they may be any shape such as spherical, needle-like, plate-like, crushed, scale-like, etc., and there is no problem even if they are aggregates of these. The inorganic fillers shown above are not limited to these, and further, they may be used alone or in combination of two or more.

[0070] There is no particular restriction on the particle size of the inorganic filler, but considering the balance of various properties in the dental resin-reinforced glass ionomer cement composition of the present invention, it is preferable that the 50% particle size (D50) is 0.01 μm or more and 3 μm or less. If the 50% particle size (D50) of the inorganic filler is less than 0.01 μm, the inorganic filler cannot be highly filled in the (e1) organic-inorganic composite filler, and the wear resistance of the dental resin-reinforced glass ionomer cement composition of the present invention may decrease. In addition, if the 50% particle size (D50) of the inorganic filler exceeds 3 μm, the polishability of the dental resin-reinforced glass ionomer cement composition of the present invention may decrease, and a smooth surface may not be obtained. In the dental resin-reinforced glass ionomer cement composition of the present invention, the inorganic filler constituting the (e1) organic-inorganic composite filler may be composed only of an inorganic filler having a 50% particle size (D50) of 0.01 μm or more and 3 μm or less.

[0071] It is preferable to subject these inorganic fillers to a surface treatment to make them hydrophobic. This surface treatment allows for a high loading of the inorganic filler in the (e1) organic-inorganic composite filler, thereby improving the mechanical properties of the (e1) organic-inorganic composite filler itself. There are no particular limitations on the surface treatment agent that can be used for the surface treatment of the inorganic filler, and known agents such as organosilicon compounds, organozirconium compounds, and organotitanium compounds can be used, but organosilicon compounds are the most commonly used. Specific examples of the organosilicon compound include methyltrimethoxysilane, ethyltrimethoxysilane, methoxytripropylsilane, propyltriethoxysilane, hexyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyltri(β-methoxyethoxy)silane, γ-(meth)acryloyloxypropyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, methyltrichlorosilane, phenyltrichlorosilane, trimethylsilylisocyanate, vinylsilyltriisocyanate, phenylsilyltriisocyanate, and hexamethyldisilazane, but are not limited thereto. These surface treatment agents can be used alone or in combination. The surface treatment method is not particularly limited, and known methods can be applied. Furthermore, the amount of the surface treatment agent relative to the inorganic filler when performing the surface treatment is not particularly limited, and may be appropriately adjusted depending on the particle size of the inorganic filler, etc.

[0072] The content of the inorganic filler contained in the raw material of the (e1) organic inorganic composite filler is preferably 10% by mass or more and 85% by mass or less, more preferably 40% by mass or more and 85% by mass or less. If the content of the inorganic filler in the (e1) organic inorganic composite filler is less than 10% by mass, the wear resistance of the dental resin-reinforced glass ionomer cement composition of the present invention may decrease. On the other hand, if the content of the inorganic filler exceeds 85% by mass, the dispersion of the inorganic filler in the (e1) organic inorganic composite filler becomes insufficient, and the mechanical properties of the dental resin-reinforced glass ionomer cement composition of the present invention may decrease. In the dental resin-reinforced glass ionomer cement composition of the present invention, the (e1) organic inorganic composite filler can contain 10% by mass or more and 85% by mass or less of an inorganic filler having a 50% particle size (D50) of 0.01 μm or more and 3 μm or less. The dental resin-reinforced glass ionomer cement composition of the present invention can contain, as the (e1) organic-inorganic composite filler, only an organic-inorganic composite filler in which the content of the inorganic filler contained in the raw materials is 10% by mass or more and 85% by mass or less.The dental resin-reinforced glass ionomer cement composition of the present invention can contain, as the (e1) organic-inorganic composite filler, only an organic-inorganic composite filler containing 10% by mass or more and 85% by mass or less of inorganic filler having a 50% particle size (D50) of 0.01 μm or more and 3 μm or less.

[0073] Next, the manufacturing method of (e1) organic inorganic composite filler will be described by taking the case where a thermal polymerization initiator is used as an example. (e1) organic inorganic composite filler is manufactured through the following main steps 1) to 4). 1) A step of mixing the components constituting (e1) organic inorganic composite filler, such as a polymerizable monomer, a thermal polymerization initiator, and an inorganic filler, to obtain a mixture; 2) A step of applying heat to the mixture to polymerize the polymerizable monomer to obtain a hardened product; 3) A step of pulverizing the hardened product as necessary to obtain an organic inorganic composite filler; and 4) A step of subjecting the organic inorganic composite filler to a surface treatment as necessary. In the dental resin-reinforced glass ionomer cement composition of the present invention, the ground organic inorganic composite filler obtained in step 3) may be used as it is, or the surface-treated organic inorganic composite filler obtained in step 4) may be used.

[0074] The step of obtaining a mixture of each component in step 1) includes, but is not limited to, a method of mixing each component such as a polymerizable monomer, a thermal polymerization initiator, and an inorganic filler using a kneader, a method of aggregating an inorganic filler to obtain an aggregated filler having pores of several μm to several tens of μm, then immersing the aggregated filler in a solution in which a thermal polymerization initiator and a polymerizable monomer are dissolved in an organic solvent to form a slurry, and then removing the organic solvent at a low temperature and under reduced pressure to allow the polymerizable monomer to penetrate and cover the inside and surface of the aggregated filler, thereby mixing each component, or a method of press-molding an inorganic filler to obtain an inorganic filler molded body, immersing the molded body in a polymerizable monomer containing a thermal polymerization initiator, and allowing the polymerizable monomer to penetrate the inside of the molded body to mix each component. In addition, in this step, the surface treatment of the inorganic filler and the mixing of each component can be performed simultaneously by dissolving a surface treatment agent such as the above-mentioned organic silicon compound in the polymerizable monomer. This makes it possible to omit the step of surface treating the inorganic filler before mixing each component.

[0075] In the step of obtaining a cured product in step 2), the polymerization temperature and polymerization time may be appropriately adjusted according to the properties of the thermal polymerization initiator used and based on the heat-induced discoloration of the organic-inorganic composite filler and the amount of residual unpolymerized monomer, but generally the polymerization temperature is 70° C. or higher and 150° C. or lower, and the polymerization time is several minutes to several hours. Also, polymerization conditions such as polymerization in air, polymerization in an inert gas atmosphere such as nitrogen or argon, polymerization under normal pressure, or polymerization under pressure can be appropriately selected according to the polymerization method.

[0076] In step 3) of obtaining an organic-inorganic composite filler by pulverization, the same pulverization method as that used in producing the above-mentioned (a) acid-reactive glass powder can be adopted. (e1) The 50% particle size (D50) of the organic-inorganic composite filler is not particularly limited, but in order to effectively reduce stringiness of the kneaded product in the dental resin-reinforced glass ionomer cement composition of the present invention, the 50% particle size (D50) is preferably 1 μm or more and 50 μm or less. (e1) If the 50% particle size (D50) of the organic-inorganic composite filler is less than 1 μm, the kneadability may decrease, and if the 50% particle size (D50) is more than 50 μm, the mechanical properties may decrease.

[0077] In step 4) of subjecting the organic-inorganic composite filler to a surface treatment, the same surface treatment agent as that which can be used for the surface treatment of the inorganic filler described above can be used. In addition, a known method can be applied for the surface treatment method as well as the surface treatment of the inorganic filler. Furthermore, there is no particular restriction on the amount of the surface treatment agent relative to the organic-inorganic composite filler when performing the surface treatment, and it may be appropriately adjusted according to the particle size of the organic-inorganic composite filler, but it is preferably 0.1 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the organic-inorganic composite filler.

[0078] <(e2) Porous organic filler> The (e2) porous organic filler that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention is not particularly limited in its component composition, and particles made of various polymers can be used as long as they have a large number of pores on their surface. More specifically, the above-mentioned (meth)acryloyloxy group or (meth)acrylamide group-containing monofunctional polymerizable monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, butyl (meth)acrylate, or 2-ethylhexyl (meth)acrylate, and other monofunctional polymerizable monomers such as α-methylstyrene, isoprene, butadiene, isobutylene, vinyl acetate, vinyl chloride, vinyl alcohol, ethylene, or propylene can be homopolymerized or copolymerized, but is not limited thereto. In addition, these may be either non-crosslinked polymer particles or polymer particles crosslinked by a crosslinkable polymerizable monomer.

[0079] (e2) There are no particular limitations on the 50% particle size (D50), average pore size, and specific surface area of ​​the porous organic filler. However, in order to effectively reduce stringiness of the kneaded product in the dental resin-reinforced glass ionomer cement composition of the present invention, the 50% particle size (D50) is 1 μm or more and 50 μm or less, the average pore size is 1 nm or more and 100 nm or less, and the specific surface area is 30 m or less. 2 / g or more 500m 2 It is preferable that the molecular weight is not more than 1 / g.

[0080] (e2) When the 50% particle size (D50) of the porous organic filler is less than 1 μm, the kneadability may decrease, and when the 50% particle size (D50) exceeds 50 μm, the mechanical properties may decrease. In addition, when the average pore size of the porous organic filler (e2) is less than 1 nm, the effect of reducing stringiness of the kneaded product may not be sufficiently obtained, and when the average pore size exceeds 100 nm, the mechanical properties may decrease. Furthermore, when the specific surface area of ​​the porous organic filler (e2) is less than 30 m 2If the specific surface area is less than 500 m 2 When the density exceeds 100 / g, a uniform kneaded product cannot be obtained, and mechanical properties may be deteriorated. The dental resin-reinforced glass ionomer cement composition of the present invention further comprises (e2) a porous organic filler having a 50% particle size (D50) of 1 μm or more and 50 μm or less, an average pore size of 1 nm or more and 100 nm or less, and a specific surface area of ​​30 m 2 / g or more 500m 2 The porous organic filler may contain only porous organic fillers having a molecular weight of up to 1 / g.

[0081] The (e1) organic-inorganic composite filler and / or the (e2) porous organic filler can be used alone or in combination. The (e1) organic-inorganic composite filler and / or the (e2) porous organic filler must be contained in an amount of 1% by mass or more and 30% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, based on the total amount of the dental resin-reinforced glass ionomer cement composition of the present invention. If the content of the (e1) organic-inorganic composite filler and / or the (e2) porous organic filler is less than 1% by mass, the effect of reducing the stringiness of the kneaded product cannot be sufficiently obtained. If the content exceeds 30% by mass, the mechanical properties of the cured product are reduced. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain the (e1) organic-inorganic composite filler and may contain the (e2) porous organic filler. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain the (e2) porous organic filler and may contain the (e1) organic-inorganic composite filler. The dental resin-reinforced glass ionomer cement composition of the present invention may contain both (e1) an organic-inorganic composite filler and (e2) a porous organic filler. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain any filler other than (e1) the organic-inorganic composite filler. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain any filler other than (e2) the porous organic filler. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain any filler other than (e1) the organic-inorganic composite filler and (e2) the porous organic filler.

[0082] <(f) Polymerization initiator> The polymerization initiator (f) that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention is not particularly limited, and any known polymerization initiator used in the dental field can be used without any restriction. The polymerization initiator (f) can be a redox initiator that initiates radical polymerization by the action of a compound of two or more components (sometimes called a "chemical polymerization initiator" in the dental field. Hereinafter, it will be referred to as a "chemical polymerization initiator"), or a photopolymerization initiator that initiates radical polymerization by light irradiation (photopolymerization initiator). In the present invention, any polymerization initiator can be used without any restriction. As long as the polymerization initiator (f) can sufficiently polymerize the polymerizable monomer (d), there is no particular restriction on the method of blending the polymerization initiator (f) in the dental resin-reinforced glass ionomer cement composition of the present invention. For example, when the dental resin-reinforced glass ionomer cement composition of the present invention is composed of a powder material and a liquid material, or a first paste and a second paste, the polymerization initiator (f) may be blended in both of them, or in either the powder material and the liquid material, or the first paste and the second paste. The dental resin-reinforced glass ionomer cement composition of the present invention may contain only a chemical polymerization initiator as the polymerization initiator (f). The dental resin-reinforced glass ionomer cement composition of the present invention may not contain a chemical polymerization initiator as the polymerization initiator (f). The dental resin-reinforced glass ionomer cement composition of the present invention may contain only a photopolymerization initiator as the polymerization initiator (f). The dental resin-reinforced glass ionomer cement composition of the present invention may not contain a photopolymerization initiator as the polymerization initiator (f). The dental resin-reinforced glass ionomer cement composition of the present invention may contain only a chemical polymerization initiator and a photopolymerization initiator as the polymerization initiator (f). The dental resin-reinforced glass ionomer cement composition of the present invention may contain a chemical polymerization initiator and a photopolymerization initiator as the polymerization initiator (f).

[0083] Examples of the chemical polymerization initiator include, but are not limited to, peroxide / amine compound, peroxide / amine compound / aromatic sulfinic acid or its salt, or aromatic sulfonyl compound, peroxide / amine compound / (thio)barbituric acid compound or (thio)barbiturate compound, peroxide / amine compound / borate compound, peroxide / ascorbic acid compound, peroxide / thiourea / vanadium compound or copper compound, (thio)barbituric acid compound / organometallic compound / organohalogen compound, aromatic sulfinic acid salts that initiate radical polymerization by the action of an acidic compound, borate compounds, or (thio)barbiturates, and a combination of an acidic compound, and further organic boron compounds that initiate radical polymerization by reacting with oxygen or water.

[0084] Examples of peroxides include sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium peroxodiphosphate, potassium peroxodiphosphate, ammonium peroxodiphosphate, diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, monoperoxycarbonates, peroxyketals, dialkyl peroxides, hydroperoxides, and ketone peroxides. More specific examples of the peroxide include benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, diacetyl peroxide, lauroyl peroxide, di-t-butyl peroxide, dicumyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-amyl hydroperoxide, isopropylbenzene hydroperoxide, 5-phenyl-4-pentenyl hydroperoxide, t-butylperoxyisopropyl carbonate, methyl ethyl ketone peroxide, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and t-butyl peroxybenzoate, but are not limited thereto.

[0085] The amine compound is preferably an aromatic secondary or aromatic tertiary amine, and specific examples thereof include N-methyl-p-toluidine, N-ethyl-p-toluidine, N-(2-hydroxyethyl)-p-toluidine, ethyl p-methylaminobenzoate, N-methylaniline, N-ethylaniline, N-(2-hydroxyethyl)aniline, N,N-dimethylaniline, N,N-diethylaniline, N,N-bis(2-hydroxyethyl)aniline, N-(2-hydroxyethyl)-N-methylaniline, N-ethyl-N-(2-hydroxyethyl)aniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl p-dimethylaminobenzoate, and the like, but are not limited thereto.

[0086] Examples of aromatic sulfinic acids or salts thereof, or aromatic sulfonyl compounds include benzenesulfinic acid, p-toluenesulfinic acid, o-toluenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and sodium salts, potassium salts, lithium salts, or ammonium salts thereof, or benzenesulfonyl chloride, benzenesulfonyl fluoride, benzenesulfonamide, benzenesulfonyl hydrazide, p-toluenesulfonyl chloride, p-toluenesulfonyl fluoride, p-toluenesulfonamide, p-toluenesulfonyl hydrazide, and the like, but are not limited to these.

[0087] Examples of (thio)barbituric acid compounds or (thio)barbiturate compounds include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 5-laurylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, and the like. Examples of barbituric acid include, but are not limited to, xylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-phenyl-5-benzylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, thiobarbituric acid, 1,3-dimethylthiobarbituric acid, 5-phenylthiobarbituric acid, and their alkali metal salts (lithium, sodium, potassium salts, etc.), alkaline earth metal salts (calcium, strontium, barium salts, etc.), ammonium salts, tetramethylammonium salts, and tetraethylammonium salts.

[0088] Examples of borate compounds include trialkylphenyl boron, trialkyl(p-chlorophenyl) boron, trialkyl(p-fluorophenyl) boron, trialkyl(p-butylphenyl) boron, trialkyl(p-butyloxyphenyl) boron, monoalkyltriphenyl boron, monoalkyltris(p-chlorophenyl) boron, monoalkyltris(p-fluorophenyl) boron, monoalkyltris(p-butylphenyl) boron, monoalkyltris(p-butyloxyphenyl) boron, tetraphenyl boron, and tetrakis Examples of the salt include, but are not limited to, sodium salts, potassium salts, lithium salts, magnesium salts, tetramethylammonium salts, tetraethylammonium salts, tetrabutylammonium salts, methylpyridinium salts, ethylpyridinium salts, methylquinolinium salts, and ethylquinolinium salts of (p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis(p-butylphenyl)boron, and tetrakis(p-butyloxyphenyl)boron (wherein the alkyl group is an n-butyl group, an n-octyl group, an n-dodecyl group, or the like).

[0089] Examples of ascorbic acid compounds include, but are not limited to, L(+)-ascorbic acid, isoascorbic acid, sodium L(+)-ascorbate, potassium L(+)-ascorbate, calcium L(+)-ascorbate, sodium isoascorbate, and the like.

[0090] Examples of thiourea compounds include, but are not limited to, 1,3-dimethylthiourea, tetramethylthiourea, 1,1-diethylthiourea, 1,1,3,3-tetraethylthiourea, 1-allyl-2-thiourea, 1,3-diallylthiourea, 1,3-dibutylthiourea, 1,3-diphenyl-2-thiourea, 1,3-dicyclohexylthiourea, ethylenethiourea, N-methylthiourea, N-phenylthiourea, N-benzoylthiourea, and N-acetylthiourea.

[0091] Examples of vanadium compounds include, but are not limited to, vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, and the like.

[0092] Examples of copper compounds include, but are not limited to, copper acetate, copper salicylate, copper gluconate, copper oleate, copper benzoate, copper acetylacetonate, and copper naphthenate.

[0093] Examples of the organometallic compound include, in addition to the copper compounds, manganese acetylacetone, manganese naphthenate, manganese octoate, cobalt acetylacetone, cobalt naphthenate, lithium acetylacetone, lithium acetate, zinc acetylacetone, zinc naphthenate, nickel acetylacetone, nickel acetate, aluminum acetylacetone, calcium acetylacetone, iron acetylacetone, chromium acetylacetone, and sodium naphthenate, but are not limited to these.

[0094] Examples of organic halogen compounds include, but are not limited to, tetramethylammonium chloride, tetraethylammonium chloride, trioctylmethylammonium chloride, dilauryldimethylammonium chloride, lauryldimethylbenzylammonium chloride, tetra-n-butylammonium chloride, benzyldimethylcetylammonium chloride, and benzyldimethylstearylammonium chloride.

[0095] As the acidic compound to be reacted with aromatic sulfinates, borate compounds, or (thio)barbiturates, any of inorganic acids and organic acids can be used without any limitation, but it is preferable to use an organic acid. Furthermore, from the viewpoint of the stability of the cured product, it is most preferable to use an organic acid having a polymerizable group, that is, an acidic group-containing polymerizable monomer. The acidic group-containing polymerizable monomer is not particularly limited in the type or number of the polymerizable group or acidic group, and those generally used in the dental field can be used. Examples of the acidic group include a carboxy group, a phosphoric acid group, a phosphonic acid group, and a sulfonic acid group. Representative examples of the acidic group-containing polymerizable monomer used in the dental field include, but are not limited to, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, and 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid. These acidic compounds may be used alone or in combination of two or more.

[0096] Examples of organic boron compounds that react with oxygen or water to initiate polymerization include trialkylborons such as triethylboron, tri(n-propyl)boron, triisopropylboron, tri(n-butyl)boron, tri(s-butyl)boron, triisobutylboron, tripentylboron, trihexylboron, and tricyclohexylboron, as well as partial oxides thereof, but are not limited to these.

[0097] Examples of the photopolymerization initiator include those made of a photosensitizer, photosensitizer / photopolymerization accelerator, etc. Specific examples of the photosensitizer include α-diketones such as benzil, camphorquinone, α-naphthyl, acetonaphthene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, and naphthoquinone, benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, and 2-methylthioxanthone. Thioxanthones such as thioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; benzophenone, p-chlorobenzophenone, p-methoxybenzophenone, and other benzophenones; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, and other benzophenones; acylphosphine oxides such as bis(2,6-dimethoxybenzoyl)phenylphosphine oxide; α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1; ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, and benzyl (2-methoxyethyl ketal); 3-(4-methoxybenzoyl)coumarin, 3-benzoyl-5,7-dimeth- coumarins such as 3,3'-oxycoumarin, 3,3'-carbonylbis(7-diethylaminocoumarin), and 3,3'-carbonylbis(7-dibutylaminocoumarin); titanocenes such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, and bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium, but are not limited thereto.

[0098] Specific examples of the photopolymerization accelerator include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylanthranilic acid methyl ester, N,N-dihydroxyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl -α-naphthylamine, N,N-dimethyl-β-naphthylamine, triethanolamine, tributylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tertiary amines such as 2,2'-(n-butylimino)diethanol, secondary amines such as N-phenylglycine, barbituric acids such as 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1,3,5-trimethylbarbituric acid, sodium 1,3,5-trimethylbarbiturate, and calcium 1,3,5-trimethylbarbiturate, 2,4,6-tris(trichloromethyl)-s-triazine, 2- Phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,Triazine compounds such as 6-bis(trichloromethyl)-s-triazine, diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis-(4-methylphenyl)iodonium hexafluorophosphate, bis-(4-methylphenyl)iodonium hexafluoroantimonate, bis-(4-methylphenyl)iodonium tetrakis(pentafluorophenyl)borate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, Examples of the dialkyl iodonium salts include diaryliodonium salts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin diversatate, dioctyltin bis(mercaptoacetic acid isooctyl ester) salt, and tin compounds such as tetramethyl-1,3-diacetoxydistannoxane; aldehyde compounds such as lauryl aldehyde and terephthalaldehyde; and sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decanethiol, and thiosalicylic acid, but are not limited to these.

[0099] Furthermore, in order to improve the photopolymerization promoting ability, in addition to the above photopolymerization accelerators, it is effective to add oxycarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxyisobutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, and dimethylolpropionic acid, but the addition is not limited to these.

[0100] In addition, these (f) polymerization initiators can be used alone or in combination of several kinds, regardless of the polymerization mode or polymerization method. In addition, these (f) polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules as necessary without any problem.

[0101] The content of the polymerization initiator (f) is preferably 0.01% by mass or more and 10% by mass or less, and more preferably 0.1% by mass or more and 5% by mass or less, based on the total content of the dental resin-reinforced glass ionomer cement composition of the present invention. If the content of the polymerization initiator (f) is less than 0.01% by mass, the hardening property may deteriorate and the mechanical properties may decrease. If the content of the polymerization initiator (f) is more than 10% by mass, the storage stability may deteriorate.

[0102] <Other ingredients> The dental resin-reinforced glass ionomer cement composition of the present invention can contain any acidic compound for the purpose of adjusting the operation time and hardening time, and the type of the acidic compound is not particularly limited. Specific examples of these acidic compounds include carboxylic acid compounds such as tartaric acid, citric acid, maleic acid, fumaric acid, malic acid, aconitic acid, tricarballylic acid, itaconic acid, 1-butene-1,2,4-tricarboxylic acid, and 3-butene-1,2,3-tricarboxylic acid, phosphoric acid, pyrophosphoric acid, and tripolyphosphoric acid, and metal salts of these acidic compounds, but are not limited thereto. In addition, these acidic compounds can be used alone or in combination. When an acidic compound is contained in the dental resin-reinforced glass ionomer cement composition of the present invention, the acidic compound is preferably contained in an amount of 0.1% by mass or more and 15% by mass or less based on the entire composition.

[0103] Furthermore, the dental resin-reinforced glass ionomer cement composition of the present invention may contain any surfactant within a range that does not affect various properties, for the purpose of adjusting the initial compatibility and kneaded properties of the powder material and liquid material, or the first paste and second paste, etc. The surfactant that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention may be either an ionic surfactant or a nonionic surfactant.

[0104] Specific examples of ionic surfactants include anionic surfactants such as metal salts of aliphatic carboxylic acids, such as sodium stearate, sulfated metal salts of aliphatic carboxylic acids, such as sodium dioctyl sulfosuccinate, and metal salts of higher alcohol sulfates, such as sodium stearyl sulfate. Cationic surfactants include adducts of higher alkylamines and ethylene oxide, amines made from lower amines, and alkyltrimethylammonium salts, such as lauryltrimethylammonium chloride. Amphoteric surfactants include metal salts of higher alkylaminopropionic acids, such as sodium stearylaminopropionate, and betaines, such as lauryldimethylbetaine.

[0105] Examples of nonionic surfactants include polyethylene glycol type or polypropylene glycol type surfactants in which ethylene oxide or propylene oxide is added to higher alcohols, alkylphenols, fatty acids, higher aliphatic amines, aliphatic amides, etc., and polyhydric alcohol type surfactants in which polyhydric alcohols, diethanolamines, sugars and fatty acids are ester-bonded.

[0106] The surfactants shown above are not limited to these, and may be used alone or in combination. When the dental resin-reinforced glass ionomer cement composition of the present invention contains a surfactant, the surfactant is preferably contained in an amount of 0.001% by mass or more and 5% by mass or less based on the total composition. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain a surfactant.

[0107] Furthermore, when the dental resin-reinforced glass ionomer cement composition of the present invention is in a paste form, a thickener can be optionally contained for the purpose of adjusting the paste properties within a range that does not adversely affect various characteristics.

[0108] The thickener that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention may be either an inorganic thickener or an organic thickener. Examples of the inorganic thickener include fumed silica, calcium carbonate, calcium silicate, magnesium silicate, and clay minerals such as saponite, montmorillonite, beidellite, vermiculite, sauconite, stevensite, hectorite, smectite, tietite, and sepiolite.

[0109] Examples of organic thickeners include methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, calcium carboxymethyl cellulose, carboxypolymethylene, sodium alginate, propylene glycol alginate, sodium polyacrylate, starch, sodium starch glycolate, starch phosphate, polyvinylpyrrolidone, carboxyvinyl polymer, khaya gum, gum arabic, karaya gum, guar gum, and xanthan gum.

[0110] The thickeners shown above are not limited to these, and may be used alone or in combination. When the dental resin-reinforced glass ionomer cement composition of the present invention contains a thickener, the thickener is preferably contained in the paste at 0.001% by mass or more and 10% by mass or less. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain a thickener.

[0111] Furthermore, the dental resin-reinforced glass ionomer cement composition of the present invention may optionally contain a non-acid-reactive inorganic powder for the purpose of adjusting the operability, mechanical properties, or hardening properties, as long as the powder does not adversely affect the various properties.

[0112] The non-acid-reactive inorganic powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be used without any particular limitation as long as it does not contain an element that reacts with the acidic group of the (b) polyalkenoic acid. In addition, the shape of the non-acid-reactive inorganic powder is not particularly limited, and it may be any shape such as a spherical, needle-like, plate-like, crushed, or scaly particle shape, or an aggregate thereof. There is no particular limitation on the 50% particle size (D50) of these non-acid-reactive inorganic powders, but it is preferably 0.001 μm or more and 20 μm or less.

[0113] Specific examples of non-acid-reactive inorganic powders include quartz, amorphous silica, ultrafine silica particles, various glasses that do not contain elements that react with acidic groups (including glasses produced by the fusion method, synthetic glasses by the sol-gel method, glasses produced by gas-phase reactions, etc.), silicon nitride, silicon carbide, boron carbide, etc., but are not limited to these, and furthermore, they can be used alone or in combination of several kinds.

[0114] When the dental resin-reinforced glass ionomer cement composition of the present invention contains a non-acid-reactive inorganic powder, the content of the non-acid-reactive inorganic powder is preferably 0.001% by mass or more and 20% by mass or less based on the total composition. The dental resin-reinforced glass ionomer cement composition of the present invention may not contain the non-acid-reactive inorganic powder.

[0115] In addition, the dental resin-reinforced glass ionomer cement composition of the present invention may contain any of the following components as necessary: ​​a polymerization inhibitor, a chain transfer agent, a discoloration inhibitor, an ultraviolet absorber, a preservative, an antibacterial agent, a colorant, a fluorescent agent, an inorganic fiber material, an organic fiber material, and other conventionally known additives.

[0116] The dental resin-reinforced glass ionomer cement composition of the present invention can be provided in various forms, such as powder / liquid, paste / paste, or paste / liquid, so long as (a) the acid-reactive glass powder and (b) the polyalkenoic acid do not coexist in the presence of (c) water.

[0117] In the dental resin-reinforced glass ionomer cement composition of the present invention, it is preferable to shorten the shaping start time and the treatment time by adjusting the blending amount of each component shown above, etc. In order to shorten the treatment time, the shaping start time is preferably within 30 seconds, and more preferably within 20 seconds.

[0118] The dental resin-reinforced glass ionomer cement composition of the present invention can be used for a wide range of applications in dental treatment, such as as a filling material and a bonding material, as well as a pit and fissure sealant, a lining material, and abutment construction material. EXAMPLES

[0119] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. Components (a) to (f) and other components used to prepare the dental resin-reinforced glass ionomer cement compositions of the examples and comparative examples, as well as their abbreviations and production methods, are as follows:

[0120] [(a) Acid-reactive glass powder] G1: Acid-reactive glass powder 1 (G1) (fluoroaluminosilicate glass powder, 50% particle size (D50): 2.5 μm) G2: Acid-reactive glass powder 2 (G2) (silane-treated fluoroaluminosilicate glass powder, 50% particle size (D50): 2.5 μm) G3: Acid-reactive glass powder 3 (G3) (silane-treated fluoroaluminosilicate glass powder, 50% particle size (D50): 30 μm) G4: Acid-reactive glass powder 4 (G4) (silane-treated fluoroaluminosilicate glass powder, 50% particle size (D50): 0.45 μm)

[0121] [(b) Polyalkenoic acid] PCA1: Acrylic acid homopolymer powder (weight average molecular weight: 50,000) PCA2: Acrylic acid homopolymer powder (weight average molecular weight: 15,000) PCA3: Acrylic acid homopolymer powder (weight average molecular weight: 350,000)

[0122] [(c)Water] ·IEW: Ion-exchanged water

[0123] [(d) Polymerizable monomer] GDMA: Glycerol-1,3-dimethacrylate (hydroxyl group-containing polymerizable monomer) HEMA: 2-hydroxyethyl methacrylate (hydroxyl group-containing polymerizable monomer) 4-AET: 4-acryloxyethyl trimellitic acid (polymerizable monomer containing an acidic group) FAM: 4-functional acrylamide monomer ("FOM-03006" (FUJIFILM Wako Pure Chemical Industries, Ltd.)) Bis-GMA: Bisphenol A diglycidyl methacrylate (hydroxyl group-containing polymerizable monomer)

[0124] [(e1) Organic-inorganic composite filler] O1: Organic-inorganic composite filler 1 (50% particle size (D50): 30 μm, inorganic filler content: 50% by mass, primary average particle size of inorganic filler: 16 nm, polymerizable monomer: 50% by mass) O2: organic-inorganic composite filler 2 (50% particle size (D50): 25 μm, inorganic filler content: 25 mass%, primary average particle size of inorganic filler: 16 nm, polymerizable monomer: 75 mass%) O3: Organic-inorganic composite filler 3 (50% particle size (D50): 20 μm, inorganic filler content: 50% by mass, 50% particle size (D50) of inorganic filler: 0.5 μm, polymerizable monomer: 50% by mass) O4: Organic-inorganic composite filler 4 (50% particle size (D50): 55 μm, inorganic filler content: 75% by mass, 50% particle size (D50) of inorganic filler: 4 μm, polymerizable monomer: 25% by mass) [(e2) Porous organic filler] PO1: Spherical porous cross-linked polymethyl methacrylate (Techpolymer XX5958Z, manufactured by Sekisui Chemical Co., Ltd.), 50% particle size (D50): 5 μm, average pore size: 5 nm, specific surface area: 73 m2 / g) ·PO2: Spherical porous cross-linked polystyrene ("Techpolymer MBP" (manufactured by Sekisui Plastics Co., Ltd.), 50% particle size (D50): 8 μm, average pore size: 20 nm, specific surface area: 85 m 2 / g)

[0125] [(f) Polymerization initiator] ·KPS: Potassium peroxodisulfate ·TSNa: Sodium p-toluenesulfinate ·AA: L(+)-Ascorbic Acid CQ: dl-Camphorquinone

[0126] [others] Silica M: Non-acid reactive inorganic powder Silica filler (50% particle size (D50): 30μm) D250: Spherical non-porous polyethyl methacrylate ("Hyperal D-250E" (manufactured by Negami Chemical Industries, Ltd.), 50% particle size (D50): 40 μm) Aerosil R972: Fumed silica (average primary particle size: 16 nm) ·TA: Tartaric acid

[0127] [(a) Preparation of acid-reactive glass powder] [Production of acid-reactive glass powder 1 (G1)] Various raw materials of silica, alumina, aluminum phosphate, sodium fluoride, and strontium carbonate (glass composition: SiO 2 26.4% by mass, Al 2 O 3 29.3% by mass, SrO 20.5% by mass, P 2 O 5 10.9% by mass, Na 2After mixing 2.5% by mass of O and 10.4% by mass of F, the raw material mixture was melted in a melting furnace at 1400°C. The melt was removed from the melting furnace and quenched in water to obtain fluoroaluminosilicate glass. The obtained fluoroaluminosilicate glass was pulverized until the 50% particle size (D50) was 2.5 μm to obtain acid-reactive glass powder 1 (G1). The 50% particle size (D50) was measured using a laser diffraction particle sizer (Microtrac MT3300EXII: manufactured by Microtrac Bell).

[0128] [Production of acid-reactive glass powder 2 (G2)] A surface treatment liquid (total mass: 9.2 parts by mass) was prepared by mixing 1.0 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, 0.1 parts by mass of ion-exchanged water, and 8.1 parts by mass of anhydrous ethanol. This surface treatment liquid was mixed with 100 parts by mass of acid-reactive glass powder 1 (G1) in a dry state, and then heat-treated at 110°C for 5 hours using a hot air dryer to obtain acid-reactive glass powder 2 (G2).

[0129] [Production of acid-reactive glass powder 3 (G3)] Fluoroaluminosilicate glass was obtained in the same manner as for acid-reactive glass powder 1 (G1). The obtained fluoroaluminosilicate glass was pulverized until the 50% particle size (D50) was 30 μm, to obtain an acid-reactive glass powder. The 50% particle size (D50) was measured using a laser diffraction particle size measuring instrument (Microtrack MT3300EXII: manufactured by Microtrack Bell). Next, 1.0 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, 0.1 parts by mass of ion-exchanged water, and 8.1 parts by mass of anhydrous ethanol were mixed to prepare a surface treatment liquid (total mass: 9.2 parts by mass). This surface treatment liquid and 100 parts by mass of the acid-reactive glass powder were mixed in a dry state, and then heat-treated at 110 ° C. for 5 hours using a hot air dryer to obtain acid-reactive glass powder 3 (G3).

[0130] [Production of acid-reactive glass powder 4 (G4)] Fluoroaluminosilicate glass was obtained in the same manner as for acid-reactive glass powder 1 (G1). The obtained fluoroaluminosilicate glass was pulverized until the 50% particle size (D50) was 0.45 μm, to obtain an acid-reactive glass powder. The 50% particle size (D50) was measured using a laser diffraction particle size measuring instrument (Microtrack MT3300EXII: manufactured by Microtrack Bell). Next, 3.0 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, 0.3 parts by mass of ion-exchanged water, and 15.0 parts by mass of anhydrous ethanol were mixed to prepare a surface treatment liquid (total mass: 18.3 parts by mass). This surface treatment liquid and the acid-reactive glass powder were mixed in a dry state, and then heat-treated at 110 ° C. for 5 hours using a hot air dryer to obtain acid-reactive glass powder 4 (G4).

[0131] [Production of organic-inorganic composite filler 1 (O1)] 50 parts by mass of urethane dimethacrylate (hereinafter, UDMA), 50 parts by mass of neopentyl glycol dimethacrylate, and 0.1 parts by mass of benzoyl peroxide (hereinafter, BPO) were mixed to obtain a resin mixture. 50 parts by mass of the resin mixture and 50 parts by mass of Aerosil R972 were kneaded until uniform, and then the kneaded mixture was heated at 100°C for 4 hours under a nitrogen atmosphere to obtain a cured product. The obtained cured product was pulverized until the 50% particle size (D50) was 30 μm, to obtain organic-inorganic composite filler 1 (O1). The 50% particle size (D50) was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Microtrac Bell Co., Ltd.).

[0132] [Production of organic-inorganic composite filler 2 (O2)] 75 parts by mass of UDMA, 25 parts by mass of ethylene glycol dimethacrylate, and 0.2 parts by mass of BPO were mixed to obtain a resin mixture. 75 parts by mass of the resin mixture and 25 parts by mass of Aerosil R972 were kneaded until uniform, and then the kneaded mixture was heated at 100°C for 4 hours under a nitrogen atmosphere to obtain a cured product. The obtained cured product was pulverized until the 50% particle size (D50) was 25 μm, to obtain organic-inorganic composite filler 2 (O2). The 50% particle size (D50) was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Microtrac Bell).

[0133] [Production of organic-inorganic composite filler 3 (O3)] A surface treatment liquid (total mass: 17.0 parts by mass) was prepared by mixing 6.0 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, 1.0 parts by mass of ion-exchanged water, and 10.0 parts by mass of anhydrous ethanol. In addition, fluoroaluminosilicate glass was produced in the same manner as in the acid-reactive glass powder 1 (G1), and the obtained fluoroaluminosilicate glass was pulverized until the 50% particle size (D50) was 0.5 μm, thereby obtaining a fluoroaluminosilicate glass powder. The surface treatment liquid and 100 parts by mass of the fluoroaluminosilicate glass powder (50% particle size (D50): 0.5 μm) were mixed in a dry state, and then heat-treated at 110° C. for 5 hours using a hot air dryer to obtain a surface-treated glass powder. 50 parts by mass of Bis-GMA, 50 parts by mass of triethylene glycol dimethacrylate, and 0.2 parts by mass of BPO were mixed to obtain a resin mixture. 50 parts by mass of the resin mixture and 50 parts by mass of the surface-treated glass powder were kneaded until uniform, and the kneaded product was heated at 100° C. for 4 hours under a nitrogen atmosphere to obtain a cured product. The obtained cured product was pulverized until the 50% particle size (D50) was 20 μm, and an organic-inorganic composite filler 3 (O3) was obtained. The 50% particle size (D50) was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Microtrac Bell Co., Ltd.).

[0134] [Production of organic-inorganic composite filler 4 (O4)] 3.0 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, 0.5 parts by mass of ion-exchanged water, and 8.0 parts by mass of anhydrous ethanol were mixed to prepare a surface treatment liquid (total mass: 11.5 parts by mass). Next, fluoroaluminosilicate glass was obtained in the same manner as in the acid-reactive glass powder 1 (G1). The obtained fluoroaluminosilicate glass was pulverized until the 50% particle size (D50) was 4 μm, and a fluoroaluminosilicate glass powder was obtained. The surface treatment liquid and 100 parts by mass of fluoroaluminosilicate glass powder (50% particle size (D50): 4 μm) having the same components as the acid-reactive glass powder 1 (G1) were mixed in a dry state, and then heat-treated at 110° C. for 5 hours using a hot air dryer to obtain a surface-treated glass powder. 50 parts by mass of Bis-GMA, 50 parts by mass of triethylene glycol dimethacrylate, and 0.2 parts by mass of BPO were mixed to obtain a resin mixture. 25 parts by mass of the resin mixture and 75 parts by mass of the surface-treated glass powder were kneaded until uniform, and the kneaded product was heated at 100° C. for 4 hours under a nitrogen atmosphere to obtain a cured product. The obtained cured product was pulverized until the 50% particle size (D50) was 55 μm, and an organic-inorganic composite filler 4 (O4) was obtained. The 50% particle size (D50) was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Microtrac Bell Co., Ltd.).

[0135] [Preparation of powder and liquid materials, or first and second pastes] The various components were mixed in the ratios shown in Tables 1 to 5 to prepare powder materials (Tables 1 and 2), liquid materials (Table 3), a first paste (Table 4), and a second paste (Table 5).

[0136] Powder composition (mass%) used in the examples and comparative examples [Table 1]

[0137] Powder composition (mass%) used in the examples and comparative examples [Table 2]

[0138] Liquid composition (mass%) used in the examples and comparative examples [Table 3]

[0139] Composition of the first paste used in the examples and comparative examples (mass%) [Table 4]

[0140] Composition of second paste used in the examples and comparative examples (mass%) [Table 5]

[0141] [Dental resin-reinforced glass ionomer cement composition] Dental resin-reinforced glass ionomer cement compositions for filling or bonding (Examples 1 to 33, Comparative Examples 1 to 9) were prepared by combining the powder and liquid materials, or the first paste and second paste, in the powder-liquid ratios or paste ratios (w / w) shown in Tables 6, 7, 8, and 9, respectively, and were also evaluated for kneading ability, stringiness of the kneaded product, shaping start time, and compressive strength for conventional dental glass ionomer compositions (Comparative Examples 10 and 11, both for filling) that do not contain (d) polymerizable monomers and (f) polymerization initiators, i.e., do not belong to the resin-reinforced type (in the dental field, these are sometimes called "conventional type" in contrast to "resin-reinforced type"; hereafter referred to as "conventional type"). For the compositions for filling in Examples 1 to 5, 8, 9, 11 to 13, 16, 17, 20, 21, 23, 25, 27, 30, and 32, and Comparative Examples 1, 4, and 6 to 11, all of the above items were evaluated, and for the compositions for cementation in Examples 6, 7, 10, 14, 15, 18, 19, 22, 24, 26, 28, 29, 31, and 33, and Comparative Examples 2, 3, and 5, items other than the shaping start time were evaluated. The evaluation method is as follows.

[0142] [Mixability] In an environment of temperature 23±1°C and humidity 50±10%, the powder and liquid materials, or the first and second pastes of the dental resin-reinforced glass ionomer cement compositions of the Examples or Comparative Examples were mixed with a plastic spatula in the ratios shown in Tables 6, 7, 8, and 9. At this time, the time from the start of mixing to the time when the powder material was no longer visible in the mixed product and the mixed product became uniform was measured. The total amount of the powder and liquid materials, or the first and second pastes, was 360 mg. When evaluated according to the following evaluation criteria, it was determined that the product had good mixing properties when it was A or B. The evaluation was performed by three evaluators, who each performed three measurements, and the average of the measurement results was evaluated based on the following evaluation criteria to determine the evaluation result of the measurement target. -Evaluation criteria- [Powder-liquid type] A: The time required for the kneaded mixture to become uniform is less than 30 seconds. B: The time required for the kneaded mixture to become uniform is 30 seconds or more and less than 50 seconds. C: The time required for the kneaded material to become uniform is 50 seconds or longer, or the kneaded material is not uniform. [Paste type] A: The time required for the kneaded mixture to become uniform is less than 10 seconds. B: The time required for the kneaded mixture to become uniform is 10 seconds or more and less than 20 seconds. C: The time required for the kneaded mixture to become uniform is 20 seconds or more.

[0143] [Stringiness of the kneaded mixture] In an environment of temperature 23±1°C and humidity 50±10%, the powder and liquid materials, or the first and second pastes of the dental resin-reinforced glass ionomer cement compositions of the Examples or Comparative Examples were mixed with a plastic spatula in the ratios shown in Tables 6, 7, 8, and 9. The total amount of the powder and liquid materials, or the first and second pastes, was 360 mg. Immediately after mixing, the mixture was filled into a plastic simulated cavity (a 4 mm x 8 mm x 2 mm cavity simulating a Class I cavity), and the excess was scraped off to flatten the surface. 10 seconds after mixing, the cylindrical tip (diameter φ1.5 mm) of a metal instrument (Matsukaze: MiCD instrument) was vertically immersed 0.5 mm into the mixture, and the instrument was immediately gently pulled up. At this time, the degree of stringiness of the kneaded product was evaluated according to the following evaluation criteria, and it was judged that the kneaded product had good properties with little stringiness when it was rated A or B. The evaluation was performed by three evaluators three times each, and the most common evaluation result was taken as the evaluation result of the measurement target. -Evaluation criteria- A: It doesn't string. B: Slightly stringy. C: Significant stringiness.

[0144] [Possible time to start shaping] In an environment of temperature 23±1°C and humidity 50±10%, the powder and liquid materials, or the first and second pastes of the dental resin-reinforced glass ionomer cement composition of the embodiment or comparative example were mixed with a plastic spatula in the ratios shown in Tables 6, 7, 8, and 9. The total amount of the powder and liquid materials, or the first and second pastes, was 360 mg. Immediately after the mixing, the mixed material was filled into a plastic simulated cavity (a 4 mm x 8 mm x 2 mm cavity simulating a class I cavity), and the excess was scraped off to flatten the surface. The tip (diameter φ1.5 mm) of an instrument (Matsukaze: MiCD instrument) was vertically immersed 0.5 mm into the mixed material, and the instrument was immediately gently pulled up. At this time, the time until the stringiness of the mixed material was reduced and the mixed material was ready for shaping was measured at 10-second intervals, starting from the end of mixing. When evaluated according to the following evaluation criteria, products that were rated A or B were deemed to have an early molding start time. Evaluation was performed by three evaluators who each performed three measurements, and the average of the measurement results was evaluated based on the following evaluation criteria to determine the evaluation result for the measurement subject. -Evaluation criteria- A: 20 seconds after mixing is complete, the stringiness of the mixed material is reduced and shaping operations are possible. B: 30 seconds after mixing, the stringiness of the mixed material is reduced and shaping operations are possible. C: After mixing, the stringiness of the mixed material is reduced and shaping operations are possible after 40 seconds or more.

[0145] [Compressive strength] In an environment of temperature 23±1°C and humidity 50±10%, the powder and liquid materials of the dental resin-reinforced glass ionomer cement composition of the embodiment or comparative example, or the first paste and the second paste were mixed with a plastic spatula in the ratios shown in Tables 6, 7, 8, and 9. The mixed material was filled into a stainless steel mold (cylindrical with an inner diameter of 4 mm and a height of 6 mm), and irradiated with light for 10 seconds using a dental polymerization light irradiator (Penbright, manufactured by Matsukaze Co., Ltd.), and then left to stand in a thermo-hygrostat at a temperature of 37°C and a humidity of 90% or more. After standing for 1 hour, the hardened material was removed from the mold and used as a test specimen. The test specimen was immersed in ion-exchanged water at 37°C for 24 hours after the end of mixing, and the compressive strength of the test specimen was measured using an Instron universal testing machine (model: 5567A) at a crosshead speed of 1 mm / min in accordance with ISO 9917-1:2007. When evaluated according to the following evaluation criteria, it was determined that the mechanical properties were good if it was rated as A or B. Each evaluation was performed five times, and the average of the measurement results was evaluated based on the following evaluation criteria to obtain the evaluation result of the measurement subject. -Evaluation criteria- Filling Composition A: Compressive strength is 180MPa or more. B: Compressive strength is 160 MPa or more and less than 180 MPa. C: The compressive strength is less than 160 MPa. Compositions for Coalescence A: Compressive strength is 100MPa or more B: Compressive strength is 80 MPa or more and less than 100 MPa. C: The compressive strength is less than 80 MPa.

[0146] The compositions of the Examples and Comparative Examples were evaluated according to the above test methods, and the results are shown in Tables 6 to 9.

[0147] Evaluation results of Examples 1 to 11 [Table 6]

[0148] Evaluation results of Examples 12 to 22 [Table 7]

[0149] Evaluation results of Examples 23 to 33 [Table 8]

[0150] Evaluation results of Comparative Examples 1 to 11 [Table 9]

[0151] <Examples 1 to 5, 8, 9, 11 to 13, 16, 17, 20, 21, 23, 25, 27, 30, 32> Examples 1 to 5, 8, 9, 11 to 13, 16, 17, 20, 21, 23, 25, 27, 30, and 32 showed little stringiness immediately after mixing, and shaping operations could be performed soon after filling the simulated cavity. Furthermore, they showed good mixing properties and mechanical properties, and had desirable properties as a dental resin-reinforced glass ionomer cement composition for filling.

[0152] <Examples 6, 7, 10, 14, 15, 18, 19, 22, 24, 26, 28, 29, 31, 33> Examples 6, 7, 10, 14, 15, 18, 19, 22, 24, 26, 28, 29, 31, and 33 showed little stringiness immediately after mixing. Furthermore, they also showed good mixing properties and mechanical properties, and had desirable properties as a dental resin-reinforced glass ionomer cement composition for luting.

[0153] <Comparative Example 1> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 1 does not contain either (e1) an organic-inorganic composite filler or (e2) a porous organic filler. As a result of evaluating Comparative Example 1, significant stringiness occurred immediately after mixing, and it took a long time before shaping operations became possible. <Comparative Example 2> The dental resin-reinforced glass ionomer cement composition for luting of Comparative Example 2 did not contain either (e1) the organic-inorganic composite filler or (e2) the porous organic filler. As a result of evaluating Comparative Example 2, significant stringiness was observed immediately after mixing. <Comparative Example 3> The dental resin-reinforced glass ionomer cement composition for luting of Comparative Example 3 had a low content of (e1) organic-inorganic composite filler and did not contain (e2) porous organic filler. As a result of evaluating Comparative Example 3, significant stringiness was observed immediately after mixing. <Comparative Example 4> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 4 had a high content of the organic-inorganic composite filler (e1). As a result of evaluation of Comparative Example 4, the compressive strength was low. <Comparative Example 5> The dental resin-reinforced glass ionomer cement composition for luting of Comparative Example 5 had a small content of (e2) porous organic filler and did not contain (e1) organic-inorganic composite filler. As a result of evaluating Comparative Example 5, significant stringiness was observed immediately after mixing. <Comparative Example 6> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 6 has a high content of the porous organic filler (e2). As a result of evaluation of Comparative Example 6, the compressive strength was low. <Comparative Example 7> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 7 does not contain either (e1) organic-inorganic composite filler or (e2) porous organic filler, but instead contains (a) acid-reactive glass powder (G3) having a large particle size. As a result of evaluating Comparative Example 7, the compressive strength was low. <Comparative Example 8> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 8 does not contain either (e1) organic-inorganic composite filler or (e2) porous organic filler, but instead contains silica filler (silica stone M), which is a non-acid-reactive inorganic powder with a large particle size. Evaluation of Comparative Example 8 showed that there was noticeable stringiness immediately after mixing, a long time was required before shaping operations became possible, and the compressive strength was also low. <Comparative Example 9> The dental resin-reinforced glass ionomer cement composition for filling of Comparative Example 9 does not contain either (e1) organic-inorganic composite filler or (e2) porous organic filler, but instead contains non-porous organic filler (D250). As a result of evaluating Comparative Example 9, noticeable stringiness occurred immediately after mixing, a long time was required before shaping operations became possible, and the compressive strength was also low. <Comparative Example 10> Comparative Example 10 is a conventional dental glass ionomer cement composition for filling that contains (e1) an organic-inorganic composite filler but does not contain (d) a polymerizable monomer and (f) a polymerization initiator. As a result of evaluating Comparative Example 10, significant stringiness occurred immediately after mixing, a long time was required before shaping operations became possible, and the compressive strength was also low. In other words, the conventional dental glass ionomer cement composition did not exhibit the effects of the present invention, such as reduction in stringiness by blending (e1) an organic-inorganic composite filler. <Comparative Example 11> Comparative Example 11 is a conventional dental glass ionomer cement composition for filling that contains (e2) a porous organic filler but does not contain (d) a polymerizable monomer and (f) a polymerization initiator. As a result of evaluating Comparative Example 11, significant stringiness occurred immediately after mixing, a long time was required before shaping operations became possible, and the compressive strength was also low. In other words, the conventional dental glass ionomer cement composition did not exhibit the effects of the present invention, such as reduction in stringiness by blending (e2) a porous organic filler. [Industrial Applicability]

[0154] INDUSTRIAL APPLICABILITY The present invention relates to a dental resin-reinforced glass ionomer cement composition, and is a technology that can be used in the dental field.

Claims

1. (a) an acid-reactive glass powder; (b) a polyalkenoic acid, (c) water; (d) a polymerizable monomer, (e1) organic-inorganic composite filler, and / or (e2) porous organic filler: 1% by mass or more and 30% by mass or less, and (f) a polymerization initiator, A dental resin-reinforced glass ionomer cement composition comprising:

2. The (a) acid-reactive glass powder is 30% by mass or more and 80% by mass or less, (b) polyalkenoic acid: 0.5% by mass or more and 17% by mass or less; (c) Water 0.5% by mass or more and 27% by mass or less, and The (d) polymerizable monomer is 2% by mass or more and 48% by mass or less, The dental resin-reinforced glass ionomer cement composition of claim 1 , comprising:

3. 3. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein the time during which the dental resin-reinforced glass ionomer cement composition can start shaping is within 30 seconds.

4. 3. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein the (e1) organic-inorganic composite filler has a 50% particle size (D50) in the range of 1 μm or more and 50 μm or less, and contains 10% by mass or more and 85% by mass or less of inorganic filler having a 50% particle size (D50) of 0.01 μm or more and 3 μm or less.

5. The (e2) porous organic filler has a 50% particle size (D50) in the range of 1 μm to 50 μm, an average pore size of 1 nm to 100 nm, and a specific surface area of ​​30 m 2 / g or more 500m 2 3. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein the viscosity of the dental resin-reinforced glass ionomer cement composition is in the range of 0.1 to 1.0 μm / g or less.

Citation Information

Patent Citations

  • Powder liquid type dental resin reinforced glass ionomer cement composition

    JP2021031409A